Women identity formation with atypical body structure - Karpinska Ahnieshka (Borys Grinchenko Kyiv Metropolitan University, 2016)
The principal objective of the text is the attempt to answer the following question: How does a woman with abnormal body feel? It provides not only a theoretical background to the issue of human body, but also emphasizes a research aspect. The work is divided into four parts. In the first one, the way of presenting female body in culture is discussed. The second section examines the women's identity formation. Then the topic of female body image is presented. In conclusion, the results of research concerning atypical female body are analyzed.